Physical-chemical analysis of soils under different crops inthe Jataí region (GO), Brazil. - Miranda, Celeni (2025)
Particle size analysis seeks to verify the distribution of particles in the soil, whether inorganic or mineral in nature, and the quality of soils in settlements and family farming associations. Soil collections were carried out at 24 points, in 04 areas (two areas of monocultures, represented by settlements and two of polycultures, represented by associations of family farmers). The points were distributed in strategic locations oneach property. The evaluation of the soils identified the determining factors for their quality and the factors that make them impoverished and, supposedly, infertile. The analyzes were carried out in the laboratory, with the particle size being evaluated using the pipette method. Soil fertility and granulometry analyzes revealed a sandy soil, withlow fertility, requiring fertilization and liming to become fertile and productive.